Filmoteca PUCP: History and Audiovisual National Heritage - Díaz-Cervantes, Katherine (2024)
The PUCP Film Archive is the national archive representative of the International Federation of Film Archives (FIAF) and preserver of the Peruvian national heritage. This research contributes to greater knowledge and awareness of the role it plays in audiovisual preservation. In this sense, the general objective of this article is, through the case of the PUCP Film Archive, to propose a reference model for the study of film archives. The specific objectives are to delimit the areas of internal and external analysis of a film archive, to propose the SWOT methodology focused on archives, and to identify the deficiencies or limitations that the methodology has for the study of film archives.